2005
DOI: 10.1210/en.2004-1260
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony-Stimulating Factor Alleviates Adverse Consequences of Embryo Culture on Fetal Growth Trajectory and Placental Morphogenesis

Abstract: Growth factors secreted by the female reproductive tract promote development of the preimplantation embryo and potentially act as epigenetic determinants of postimplantation developmental competence and pregnancy outcome. In a comprehensive embryo transfer study in mice, we examined the late gestational and postnatal effects of embryo exposure to the cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF), identified as a key physiological regulator of cell number and viability in mouse and human bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 74 publications
11
133
1
2
Order By: Relevance
“…Moreover, some of the changes that the authors described in cloned mice were also present in a control group derived from normal zygotes exposed to the same IVC system, as the reconstructed embryos. Supporting our results, other research groups have also been reporting the incidence of increased body weights in adult mice generated from in vitro cultured embryos (Sjoblom et al, 2005). Moreover, it has also been reported that disturbance of the preimplantation embryo development may generate hypertensive offspring (Kwong et al, 2000).…”
Section: Long Term Effects Of Epigeneticsupporting
confidence: 89%
“…Moreover, some of the changes that the authors described in cloned mice were also present in a control group derived from normal zygotes exposed to the same IVC system, as the reconstructed embryos. Supporting our results, other research groups have also been reporting the incidence of increased body weights in adult mice generated from in vitro cultured embryos (Sjoblom et al, 2005). Moreover, it has also been reported that disturbance of the preimplantation embryo development may generate hypertensive offspring (Kwong et al, 2000).…”
Section: Long Term Effects Of Epigeneticsupporting
confidence: 89%
“…Therefore, treatment with GM-CSF may improve the efficiency of transgenic pig production and also the establishment of SCNT-derived embryonic stem cells. Similarly, treatment with GM-CSF improves not only blastocyst formation in vitro but also posttransfer embryonic survival in murine [40] and bovine [28] embryos. Treatment with pGM-CSF during IVC affected not only ICM cells but also TE cells and the expression of Cdx-2 mRNA in cloned blastocysts.…”
Section: Discussionmentioning
confidence: 95%
“…In addition embryos derived from these matings display perturbations in blastocyst formation which can be partially rescued using in vitro culture [13]. A definitive study by Sjoblom et al has demonstrated that addition of GM-CSF into culture media can alleviate some of the detrimental effects of embryo culture on pregnancy outcomes, such as altered placental morphogenesis [47]. The addition of many these embryotrophic growth factors to in vitro embryo culture media is now being more closely investigated for their use in human assisted reproduction to allow closer mimicry of the in vivo environment.…”
Section: Pre-implantation Embryo Developmentmentioning
confidence: 99%